Pemberdayaan Masyarakat dalam Mengatasi Hipertensi melalui Pembentukan Peer Group Penderita Hipertensi - Lindawati; Toto Subiakto; Widya Sepalanita (CV. CENDIKIA JENIUS INDONESIA, 2026)
Hypertension is a major non-communicable disease that increases the risk of cardiovascular, cerebrovascular, and renal complications, highlighting the need for community-based empowerment to improve disease control. This community service program aimed to enhance the knowledge, skills, and self-management capacity of individuals with hypertension through the establishment of peer support groups in Tanah Tinggi Village, Tangerang City. The implementation consisted of four stages: planning, preparation, implementation, and evaluation. Activities included the formation of peer groups, health education sessions, blood pressure measurement training, hypertension exercise, and continuous monitoring and evaluation. The results demonstrated an improvement in the mean knowledge score from 8.15 during the pre-test to 9.15 in the post-test and 9.90 at follow-up evaluation. Participants' competency in measuring blood pressure increased from 0% to 100%, and two active peer groups were successfully established to conduct regular education, hypertension exercise, and blood pressure monitoring. In conclusion, the peer group approach effectively improved participants' knowledge, practical skills, and community empowerment in hypertension management, thereby supporting the sustainability of community-based hypertension prevention and control programs.